Characterization of Retained Austenite in Advanced High-Strength Steel. (17th April 2023) - Li, Shouhua; Li, Kejian; Zhang, Longzhu; Feng, Yi; Liu, Ziquan; Cao, Pengjun; Liu, Bo; Dong, Jiling
Abstract : The retained austenite (RA) in advanced high-strength steels directly affects their plasticity. It is very important for the accurate characterization of their content and types. This paper prepared three specimens with three different Mn contents (1.0%, 1.4%, and 1.7%) that are used to obtain high-strength steel by ultrafast cooling heat treatment. The volume content and distribution of the RA were analysed by an X-ray Debye ring measurement system, electron backscatter diffraction (EBSD), and transmission electron microscopy (TEM). In addition, the mechanical tensile test provided the tensile properties and elongation of three specimens. It was finally concluded that when the content of Mn increased, the island-type and thin film-type RA both increased, which may effectively improve the plasticity of the martensitic steels.